Second‐Order Devolution and Administrative Exclusion in the Temporary Assistance for Needy Families Program. Issue 1 (21st February 2013) - Sheely, Amanda
<x xml:space="preserve">Abstract</x> With the passage of welfare reform in 1996, state and local governments gained substantial authority to design and implement their own welfare programs. Proponents of devolution asserted that, under devolution, local governments would be better able to tailor program administration to meet local economic needs. However, opponents contended devolution could lead to local governments seeking to control costs by limiting access to welfare. Meanwhile, existing research suggests that economics will not play an important role in determining welfare provision. This article investigates these competing claims by assessing the relationship between economic conditions and administrative exclusion, which is making programs so hard to access that potential and current recipients decide to forgo benefits, in a state that gives counties significant authority over welfare provision. To do so, I assess whether county application denial, sanctioning, and case closure rates are influenced by changes in local economic characteristics. I find that, even during periods of substantial economic distress, county practices related to administrative exclusion are largely unresponsive to changes in unemployment, child poverty, and fiscal constraints. These findings call into question the responsiveness of the devolved social safety net for poor families.